2021
DOI: 10.3390/c7010025
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Mixed Amines in the CO2 Capture Process

Abstract: In order to select the best mixed amines in the CO2 capture process, the absorption of CO2 in mixed amines was explored at the required concentrations by using monoethanolamine (MEA) as a basic solvent, mixed with diisopropanolamine (DIPA), triethanolamine (TEA), 2-amino-2-methyl-1-propanol (AMP), and piperazine (PZ). Here, a bubble column was used as the scrubber, and a continuous operation was adopted. The Taguchi method was used for the experimental design. The conditional factors included the type of mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Based upon the attachment of amine groups within the molecule, it can be classified into five categories. 156 It is verified that different categories of amine have distinct advantages and drawbacks; (a) the primary amines like MEA have the advantages of a higher absorption rate for CO 2 and lower viscosity. However, they suffer from retarded absorption capacity for CO 2 (by stoichiometry 0.5 mole of CO 2 per mole of MEA) and higher heat capacity, vapor pressure, and solvent regeneration cost.…”
Section: Scope Of the Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Based upon the attachment of amine groups within the molecule, it can be classified into five categories. 156 It is verified that different categories of amine have distinct advantages and drawbacks; (a) the primary amines like MEA have the advantages of a higher absorption rate for CO 2 and lower viscosity. However, they suffer from retarded absorption capacity for CO 2 (by stoichiometry 0.5 mole of CO 2 per mole of MEA) and higher heat capacity, vapor pressure, and solvent regeneration cost.…”
Section: Scope Of the Reviewmentioning
confidence: 94%
“…Chen et al have studied CO 2 absorption in mixed amines using the Taguchi method where MEA was used as a basic solvent and mixed with diisopropanolamine (DIPA), TEA, AMP, and PZ. 156 They used 16 sets of experiments and determined the conditional factors for CO 2 absorption; the type of mixed amines, the ratio of mixed amines, liquid feed flow, the gas flow rate, and the concentration of mixed amines. Based upon the outcomes from their designed experiment, it was concluded that the optimization condition is determined by the four different parameters; absorption efficiency, absorption rate, mass transfer coefficient and scrubbing factor.…”
Section: Amine-based Solution For Co2 Capture and Its Electrochemical...mentioning
confidence: 99%
“…The reactivity of alkanolamines reduces as the number of hydrogen atoms decreases in the amine structures while the absorption capacity increases. Based on stoichiometry, the CO 2 loading capacity of primary amines is 0.5 mol of CO 2 /mol of amine [22]. It requires high energy for regeneration and is more corrosive compared to other groups of amines.…”
Section: Primary Secondary and Tertiary Aminesmentioning
confidence: 99%
“…The absorption is then followed by an energy-intensive regeneration of the amine by stripping at higher than 100 °C, where a pure CO2 gas can be released and collected. For the progress of optimizing amine scrubbing for post-combustion carbon capture, many different types of amines have been extensively screened for criteria like energy consumption for solvent regeneration, absorption performance, solvent resistance to degradation, solvent toxicity and volatility 8,9 . Among these, solvent regeneration and absorption efficiencies are considered the key criteria for assessing the performance of the amines due to the extensive energy penalty during the regeneration process of amine absorbents 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The primary and secondary amines generally react rapidly to form stable carbamates that limit the CO2 loading to 0.5 moles of CO2 per mole of amine whereas tertiary and hindered amines exhibit slower kinetics and thus form ammonium bicarbonate via base-catalyzed hydration (Reaction 1). The utilization of tertiary and hindered amines, therefore, increases the CO2 loading capacity to one mole of CO2 per mole of amine 8 .…”
Section: Introductionmentioning
confidence: 99%